The Climate-Resilient Pharmacy: Evaluating the Stability of Essential Medicines Under Extreme Heat Conditions - Jón Jónsson; Guðbjörg Ásgeirsdóttir Ólafur Sigurðsson; Ólafur Sigurðsson (Journal of Advanced Pharmaceutical Research Sciences and Sustainability (JAPRSS), 2026)
Background. Climate change is intensifying temperature variability and increasing the frequency of extreme heat events, posing significant risks to the stability of essential medicines. Pharmaceutical storage systems are traditionally designed based on controlled temperature assumptions that may no longer reflect real-world conditions, particularly in climate-vulnerable regions. Purpose. Degradation of medicines under excessive heat can reduce therapeutic efficacy and compromise patient safety. This study aims to evaluate the stability of essential medicines under extreme heat conditions and to assess the resilience of current storage practices. Method. An experimental mixed-methods design was employed, combining climate-simulated heat exposure with laboratory-based stability testing. Selected medicines representing tablets, liquid formulations, and biologics were exposed to sustained and fluctuating temperatures between 40°C and 45°C. Chemical stability, potency retention, and physical changes were measured using validated analytical instruments. Statistical analysis was conducted to identify significant differences across formulations and exposure conditions. Results. Results indicate that biologics are highly susceptible to rapid degradation, while liquid formulations show moderate instability and tablets maintain relatively higher resilience. Temperature fluctuation significantly accelerates degradation compared to constant exposure. Packaging interventions provide partial mitigation but do not fully prevent potency loss. Conclusion. Findings suggest that existing pharmaceutical storage standards are insufficient under extreme heat conditions. Development of climate-resilient storage strategies is essential to ensure drug quality and patient safety.